Methods and Implementation of Arabic Language Learning at Tadika Tunasku Sayang Al Fikh Orchard Port-Klang Selangor Malaysia - Maekong, Maplee; Chehleng, Saemsu; Ruslan, Muhammad (Yayasan Rahmat Islamiyah, 2023)
Arabic is one of the official languages of the United Nations, crucial for scholars and educators studying traditional knowledge, especially from classical texts. Furthermore, Arabic language learning also facilitates researchers and scholars in delving into Islamic sources or references (the Qur'an and Hadith). This research aims to describe the Arabic language learning skills among young children at Tadika Tunasku Sayang Al Fikh Orchard Port-Klang Selangor Malaysia. The study employs a qualitative approach with a meta-analysis method. The research findings conclude that the Arabic language learning skills among early childhood learners are based on factors like instructional media, teacher creativity, students' innovative capacity, and enrichment of learning strategies.Â Â